Bodybuilding and the use of anabolic steroids (Research, Society and Development, 2021)
This work aimed to propose a discussion about the use of anabolic steroids, without monitoring by a qualified professional, in the bodybuilding scenario. This is bibliographical research that uses as a starting point the idealization of the perfect body, propagated by social media and sought by bodybuilders, who use anabolic steroids as a faster way to achieve the desired goal. As a result of the research, the concepts, compositions of substances, as well as the description and purpose of the most used ones, allow us to see how aggressive the side effects can be to the human body, when used indiscriminately. In this sense, it is possible to conclude that the importance of work with this theme for professionals, fans of bodybuilding and even for the population as a whole is noticeable, so that the need for guidance by trained professionals to indicate the use of substances is understood, in view of the various side effects triggered by its use.